New Approaches to Cleaning of Liquid Radioactive Waste - Zabulonov, Yu.L.; Litvinenko, Yu.V.; Kadoshnikov, V.M.; Alekseeva, O.V.; Burtnyak, V.M.; Odukalets, L.A.; Borodina, N.A. (Science and Innovation, 2024)
The industrial methods for disposal of liquid radioactive waste and cleaning of contaminated solutions containing heavy metals and radionuclides have been considered. If heavy metal ions are present only in ionic form, electrodialysis has been established to be the most effective cleaning method. If the components to be removed are present in ionic and colloidal forms, the preliminary destruction of colloidal and organic matter (by hydrodynamic cavitation, low-temperature plasma method, etc.) is necessary. The developed PTANK method enables an effective purification of multicomponent metalcontaining solutions containing organic substances and complexes. The development of advanced membrane technologies and complex recycling schemes, as well as their synergistic combination will provide an opportunity to deeply clean the contaminated solutions and to minimize the secondary wastes.